Money, Regulation and Growth: Financing New Growth in Europe - Franco Bruni; Gancho Ganchev; Vladimir Tsenkov; Elena Stravrova; Cécile Bastidon; Alex Cukierman; Edward J. Kane; Mario Quagliariello; Samuel Da Rocha Lopes; Javier Villar Burke; Alessandro Scopelliti (SUERF - The European Money and Finance Forum, 2014)
On June 4-5, 2014, SUERF and Baffi Finlawmetrics jointly organised a Colloquium/Conference “Money, Regulation and Growth: Financing New Growth in Europe” at Bocconi University, Milan. The present SUERF Study includes a selection of papers based on the authors' contributions to the Milan event. The overall themes at the conference were the implications for economic growth of monetary policy, financial regulation and structural changes in European financial institutions and markets.
Keywords: E22; E44; E52; E58; G21; G28; O43; 330; economic growth; bank resolution; banking supervision; capital requirements; European Banking Authority; European Banking Union; financial crisis; financial regulation; financial stability; macroprudential policy; monetary policy; Finanzintermediation; Bankenregulierung; Geldpolitik; Finanzkrise; Wirkungsanalyse; Wirtschaftswachstum; Europa